PERAN DUKUNGAN SOSIAL DALAM MENINGKATKAN ADAPTASI PSIKOLOGIS - Innayah, Azzira; Lubis, Ramadan; Azzahra, Nazwa; Prasetyo, Ikhsan; Afrida, Elmi; Ramadhani, Syinta (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2024)
Aging is a natural process experienced by everyone and is characterized by physical, psychological and social changes. Elderly people often face problems such as declining health and independence, loss of a partner, reduced social interaction, and a decline in their role in society. The elderly face various psychological problems associated with aging, including the loss of a spouse, the absence of children, and changes in their social environment. This study investigates the role of social support in improving the psychological adaptation of the elderly. This research adopts a qualitative method, which is a scientific method often used by researchers in the field of social sciences, including education. This study investigates the impact of social support on enhancing the psychological adaptation of older adults. This study was conducted qualitatively with in-depth interviews to find out the experiences and perceptions of the elderly about the social support they receive. The results showed that social support is essential to reduce feelings of loneliness, increase a sense of security, strengthen psychological resilience, and restore their emotional and spiritual balance. The study also highlighted that strong social support can be a major crutch in dealing with the psychological challenges of old age.